Design information release under alternative design-construction modes. Issue 4 (17th July 2020) - Kalach, Mayssa; Abdul-Malak, Mohamed-Asem; Srour, Issam
Abstract : Purpose: The purpose of this paper is to analyse the impact of schedule compression under alternative project delivery methods (APDMs) on the design information release (DIR). The objectives are to understand the dynamics and the respective implications of the DIR under alternative design-construction (DC) modes (e.g. fast-track). Design/methodology/approach: The methodology of work includes: (1) identifying the relevant factors that may impact the release of design deliverables under APDMs, (2) representing the selected APDMs with corresponding DC sequencing modes and (3) conceptualizing the possible alternative dynamics of the released deliverables. Findings: The findings reveal that in contrast to the traditional one-time packaging of design deliverables, multiple DIR – with less certainty on their scope, timing, frequency and coordination quality – are released under alternative DC modes. This uncertainty mainly emanates from the deduced impact of the identified factors (e.g. DC overlapping intensity and degree of pressure by the builder) on the design deliverables dynamics. Practical implications: This study can be of benefit to Architecture/Engineering (A/E) professionals as well as to project owners in better planning for their roles and responsibilities under each of the identified modes, as it helps raising their awareness on new issues brought about by APDMs. For instance, the presented analysis indirectly informs designers, design review professionals and project owners about a potentially increased liability exposure emanating from the reduced certainty on the DIR's coordination quality. Moreover, it informs design managers about the need for a design team's re-formation and/or re-structuring (i.e. of the involved staff) in order to accommodate for the hypothesized DIR dynamics. Originality/value: This work offers a novel study that theorizes the impact of time-reduction-related factors, under alternative DC modes, on the release of design deliverables.